Design methodology for multi-degrees-of-freedom compliant mechanisms with optimal stiffness and dynamic properties - Lum, Guo Zhan (2016)
Compliant mechanisms are flexible structures that utilize elastic deformation to achieve their desired motions. Using their unique mode of actuation, compliant mechanisms can achieve highly repeatable motions that are essential for high precision micro/nano-positioning applications. As a result, they have been utilized for a wide range of applications like positioning mechanisms for high resolution imaging systems, industrial nano-imprint and nano-alignment applications, and numerous other micro/nano-manipulation tasks. The performance of the compliant mechanisms is highly dependent on their stiffness and dynamic properties because these properties dictate their workspace, transient responses and capabilities to reject disturbances. However, despite the importance of compliant mechanisms, it is still an open challenge to optimize such properties when these structures have multi-degrees-of-freedom.